2002
DOI: 10.1523/jneurosci.22-21-09595.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3Receptor Antagonism Inhibits Cocaine-Seeking and Cocaine-Enhanced Brain Reward in Rats

Abstract: dopamine D3 receptor is preferentially localized to the mesocorticolimbic dopaminergic system and has been hypothesized to play a role in cocaine addiction. To study the involvement of the D3 receptor in brain mechanisms and behaviors commonly assumed to be involved in the addicting properties of cocaine, the potent and selective D3 receptor antagonist trans-N-[4-[2-(6-cyano-1,2,3,4-tetrahydroisoquinolin-2-yl)ethyl] cyclohexyl]-4-quinolininecarboxamide (SB-277011-A) was administered to laboratory rats, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
235
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(269 citation statements)
references
References 83 publications
32
235
1
1
Order By: Relevance
“…Using this animal relapse model, we found that pretreatment with NGB 2904 (0.1, 1, and 5 mg/kg) significantly attenuated cocaine-triggered reinstatement of cocaineseeking behavior at doses that failed to reduce sucrose-plussucrose-cue-induced reinstatement of sucrose-seeking behavior, suggesting that NGB 2904-induced reduction in cocaine-seeking behavior is not caused by a generalized suppression of operant behavior. This finding is consistent with the previous finding that SB-277011A inhibits cocainetriggered reinstatement of cocaine-seeking, but not foodtriggered reinstatement of food-seeking (Vorel et al, 2002).…”
Section: Ngb 2904's Inhibition Of Cocaine-triggered Reinstatement Of supporting
confidence: 93%
See 3 more Smart Citations
“…Using this animal relapse model, we found that pretreatment with NGB 2904 (0.1, 1, and 5 mg/kg) significantly attenuated cocaine-triggered reinstatement of cocaineseeking behavior at doses that failed to reduce sucrose-plussucrose-cue-induced reinstatement of sucrose-seeking behavior, suggesting that NGB 2904-induced reduction in cocaine-seeking behavior is not caused by a generalized suppression of operant behavior. This finding is consistent with the previous finding that SB-277011A inhibits cocainetriggered reinstatement of cocaine-seeking, but not foodtriggered reinstatement of food-seeking (Vorel et al, 2002).…”
Section: Ngb 2904's Inhibition Of Cocaine-triggered Reinstatement Of supporting
confidence: 93%
“…The general procedures for electrical BSR were the same as we have reported previously (Vorel et al, 2002;Hayes et al, 2003). Briefly, after 7 days of recovery from surgery, rats were allowed to self-train (autoshape) to lever-press for rewarding BSR.…”
Section: Experimental Set 2: Electrical Brain Stimulation Reward (Bsr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Presentation of cocainepaired stimuli increased dopamine release in the nucleus accumbens and amygdala in rats (Weiss et al, 2000;Ito et al, 2000). Moreover, pretreatment with dopamine receptor antagonists prevented cue-induced cocaine-and ethanolseeking behavior (Pilla et al, 1999;Ciccocioppo et al, 2001;Liu and Weiss, 2002;Vorel et al, 2002). Although the importance of conditioned cues in the acquisition of nicotine self-administration has been demonstrated (Goldberg et al, 1981;Caggiula et al, 2001Caggiula et al, , 2002, the mechanisms underlying nicotine-seeking behavior induced by drug-associated stimuli have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%